(untitled) (Mustansiria Dental Journal, 2018)
Background: Oral squamous cell carcinoma is an aggressive malignancy. It arises from premalignant lesions followed by outgrowth of clonal cell populations with cumulative genetic alterations. Phosphoinositol 3-kinases are a family of related intracellular signal transducer enzymes capable of phosphorylating the 3 position hydroxyl group of the inositol ring of phosphatidylinositol (PtdIns). Phosphatidylinositol-3-kinases involved in cellular functions such as cell growth, proliferation, differentiation, motility, survival and intracellular trafficking, which in turn are involved in cancer. RAS is a signal transduction protein for many important cellular processes such as cellular proliferation, differentiation, and survival by mediating the cell’s response to extracellular stimulations. Kras, is a protein within the RAS family, function in the same pathway of a Ras –Raf -Mek- Erk-map kinase pathway which plays a role in mediating cellular response to cell growth. Kras appears to be involved in signal transduction and cell cycle regulation. To dates there has been limited previous investigation of protein expression of both PI3Kcb and Kras in oral squamous cell carcinoma. This study was performed to examin the expression of PI3Kcb and kras in oral squamous cell carcinoma in comparison to normal oral mucosa and to correlate the expression of both markers with clinicopathological findings including tumor grade and stage and with each other. Materials and Methods: This study included 31 selected cases of oral squamous cell carcinoma pro and retrospectively and 10 cases normal oral mucosa. PIK3cb and Kras expression has been detected by immunohistochemistry. Results: Results of the present study revealed positive PI3Kcb and kras expression in all examined oral squamous cell carcinoma cases. Immunostaining results for kras & PI3kcb were detected as brown stain for cell membrane and cytoplasm in tumor cells while there was no expression of both markers in normal oral mucosa. No significant correlation was observed between both markers and the clinicopathological finding of oral squamous cell carcinoma while highly significant positive correlation was observed between the two markers. Conclusion: The Present study provides additional evidence that Kras, and PIK3cb over expression are common in contribution to oral squamous cell carcinoma tumorigenesis, and that PI3Kcb signaling network plays an important role in oral squamous cell carcinoma and thus, pathway-specific therapies targeting these two pathways should be considered in the future treatment of oral squamous cell carcinoma patients